Analisis Pemerolehan Bahasa pada Anak Usia Dini dalam Proses Pembelajaran di TK Al Qodar - Atik wahidatul Hasanah (CV Edujavare Publishing, 2026)
This study aims to analyze the language acquisition process in early childhood within the context of learning at Al Qodar Kindergarten. This study used a qualitative approach with a case study design. The research subjects consisted of children aged 5–6 years, class teachers, and the principal of Al Qodar Kindergarten. Data collection techniques included participant observation, in-depth interviews, and documentation studies. Data validity was ensured through triangulation of sources and techniques. The results showed that children's language acquisition at Al Qodar Kindergarten occurred effectively through the integration of storytelling, singing, role-playing, and dialogic activities. These methods successfully stimulated children's vocabulary development, understanding of narrative structures, and communicative skills in meaningful contexts. The role of teachers in creating a responsive learning environment and implementing learning differentiation according to the child's individual developmental level is a crucial factor in supporting successful language acquisition. The integration of Islamic values ​​in language learning positively contributes to children's vocabulary enrichment and pragmatic understanding. However, the limited time allocated for language learning within the integrated thematic curriculum and teachers' unequal understanding of early childhood language acquisition theory pose challenges that need to be addressed. This study recommends the need for specialized training for teachers, increased time allocated for expressive language activities, and strengthening the role of the physical classroom environment as a stimulus for children's independent language development.